The Effect of Selection on the Two Important Myostatin Gene Mutations in the Dareshouri Horse in the Middle East - Reihane Seifi Moroudi; Hossein Mahboudi; Fereidoun Mahboudi (Veterinary Medicine and Science)
ABSTRACT Objective The Dareshouri horse breed is one of Iran's native equine breeds, originating from the Dareshouri tribe, a subgroup of the Qashqai nomads. This breed has a history spanning over 500 years. Horses of this breed have smooth nates, tall stature, raised tails and strong skeletal muscles. This is the first study to investigate the effect of genetics on athletic performance in the Dareshouri breed. Methods For this purpose, in this study, the genotype combination of two important variants, including the rs397152648Single nucleotide polymorphism (SNP) and Short interspersed nuclear element (SINE) insertion, was surveyed to study the effect of selection on MSTN gene mutations in this breed. Results The result displayed absence of SINE insertion and high frequency of the “C” allele in Myostatin gene (MSTN) gene in all studied horses. Considering the importance of the presence and high frequency of the rs397152648 SNP and its relationship with the low expression of equine Myostatin, the muscle mass ratio, and speed performance, this evidence confirms that the Dareshouri breed has the genetic potential to cover the race distance in a shorter time. Conclusion Given the absence of genetics studies on this valuable Iranian breed, these findings represent an important contribution to the characterisation of this breed and clearly indicate an occasion for Dareshouri horsebreeders, owners, and trainers to recognise the genetic potential of their horse to make the best decisions in breeding, selection, training and racing to improve the horse's performance.